2022
DOI: 10.1542/hpeds.2022-006690
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of Evidence Within the Medical Literature

Abstract: The quality of evidence from medical research is partially deemed by the hierarchy of study designs. On the lowest level, the hierarchy of study designs begins with animal and translational studies and expert opinion, and then ascends to descriptive case reports or case series, followed by analytic observational designs such as cohort studies, then randomized controlled trials, and finally systematic reviews and meta-analyses as the highest quality evidence. This hierarchy of evidence in the medical literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…In the hierarchy of evidence, case series provide weak evidence for causality on their own and best serve to provoke consideration for future research. Case series are, however, important for sharing experiences between clinicians and generating hypotheses that may lead to future research ( 63 ). As this is a case series, we cannot conclude whether the dietary change alone was responsible for the observed improvement in symptoms; it is not possible to assess confounding factors that may be responsible for the improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In the hierarchy of evidence, case series provide weak evidence for causality on their own and best serve to provoke consideration for future research. Case series are, however, important for sharing experiences between clinicians and generating hypotheses that may lead to future research ( 63 ). As this is a case series, we cannot conclude whether the dietary change alone was responsible for the observed improvement in symptoms; it is not possible to assess confounding factors that may be responsible for the improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest number of statistical findings presented in this scoping review come from a case–control study [ 48 ] where the data has repeatedly been analysed to address multiple hypotheses. Whilst Lara and colleagues have the largest sample of women with PCOS completing an intervention, there are inherent limitations with this study design (e.g., risk of selection bias) that reduce our confidence in the certainty of the findings [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of this systematic review was reported based on guidelines in the Preferred Reporting Items for Systematic Reviews and Meta-analysis checklist. 22,24 The AMSTAR 2 checklist also informed the conduct of the review's methodological processes. 25 with the aid of "OR" and "AND" Boolean operators, using different search terms on Tai Chi, Qigong, and TMJ.…”
Section: Methodsmentioning
confidence: 99%